Penafsiran Ayat Kursi Sebagai Media Pengobatan dan Jimat (Studi Kitab Al-Aufaq Imam Al-Ghazali) - Fakhrurrozy Erlangga; Muhammad Rizqi; Febri Wardani (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
The background of this study discusses the interpretation of Ayat Kursi (QS. Al-Baqarah: 255) as a medium of healing and amulet based on studies in the Book of al-Awfaq attributed to Imam Al-Ghazali. Ayat Kursi is known as one of the most noble verses in the Qur'an, which has many spiritual and protective virtues. The purpose of this study is to explore how this verse is positioned in Islamic supernatural healing practices and as part of amulets or tamimah, as understood in Islamic esoteric literature. The method used in this study is qualitative-descriptive with a thematic (maudhū‘i) interpretive approach and a philological study of the Al-Aufaq text. This study also examines the views of scholars on the attribution of the book to Imam Al-Ghazali and looks at its correlation with Sufi traditions and classical Islamic medicine. The results of the study show that in the Book of al-Aufaq, Ayat Kursi is not only understood theologically as tawhid and the power of Allah, but also given practical value in the form of certain letter arrangements, numbers, and diagrams (awfaq) which are believed to have metaphysical powers for protection, healing, and guarding against supernatural disturbances. Although there is debate regarding the authenticity of this book to Imam Al-Ghazali, the contents of the book reflect esoteric thinking that developed in the Islamic tradition, particularly in the realm of wisdom.